2014
DOI: 10.1038/srep07513
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine exposure and transgenerational impact: a prospective study on small regulatory microRNAs

Abstract: Early developmental stages are highly sensitive to stress and it has been reported that pre-conditioning with tobacco smoking during adolescence predisposes those youngsters to become smokers as adults. However, the molecular mechanisms of nicotine-induced transgenerational consequences are unknown. In this study, we genome-widely investigated the impact of nicotine exposure on small regulatory microRNAs (miRNAs) and its implication on health disorders at a transgenerational aspect. Our results demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 54 publications
(65 reference statements)
1
23
0
1
Order By: Relevance
“…A alta prevalência de tabagismo entre homens fumicultores sugere que o trabalho direto com o tabaco estimula o consumo do produto, para além do que acontece com os demais agricultores. Estudos recentes explicam o papel da transmissão familiar e epigenética no uso e dependência de substâncias e na manutenção de comportamentos específicos através das gerações 14,15,16 . Dessa forma, fumicultores estariam expostos à nicotina desde a vida embrionária, receberiam a herança epigenética de seus progenitores expostos à nicotina e cresceriam em um cluster familiar de adicção ao tabaco e ao álcool.…”
Section: Resultsunclassified
“…A alta prevalência de tabagismo entre homens fumicultores sugere que o trabalho direto com o tabaco estimula o consumo do produto, para além do que acontece com os demais agricultores. Estudos recentes explicam o papel da transmissão familiar e epigenética no uso e dependência de substâncias e na manutenção de comportamentos específicos através das gerações 14,15,16 . Dessa forma, fumicultores estariam expostos à nicotina desde a vida embrionária, receberiam a herança epigenética de seus progenitores expostos à nicotina e cresceriam em um cluster familiar de adicção ao tabaco e ao álcool.…”
Section: Resultsunclassified
“…39 Serum cotinine is not detected in the control animals due to the nonavailability of the substance in the serum throughout the study period, suggesting toxic impact of the studied doses upon exposure, which corroborates several previous observations. 13,18,19,48,49 Moreover, Seccareccia et al 51 reported the positive association between self-reported nicotine exposure and serum cotinine levels among the smokers, nonsmokers reporting exposure to environmental tobacco smoke (ETS), and nonsmokers with no ETS exposure even after the adjustment of age and sociodemographic and behavioral factors. Nicotine exposure from the passive tobacco smoke can also endanger plasma nicotine concentration equivalent to the levels produced by the tobacco smoking and are associated Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in corroboration with the several previous observations showing psychostimulant or drug abuse that can induce germinal cell loss including SC and spermatids, resulting in disruption of spermatogenesis. [17][18][19]53,54 Rajpurkar et al 55 claimed that CS reduces the number of germial cells, height of germinal epithelium, tubular diameter and induces apoptosis in the testis due to the presence of many toxic substances in cigarettes. 56 However, Leydig cell histology that remains unaltered upon exposure in the present study may indicate that the current doses may not be able to initiate any change in the testicular steroidogenic process; the discrepancy of which with the previous reports 57,58 may be due to the differences in the experimental design, species, strains, etc.…”
Section: Dna Damaging Potency In Testismentioning
confidence: 99%
See 2 more Smart Citations